Case report: Expansion of phenotypic and genotypic data in TENM3-related syndrome: Report of two cases - Lu, Fen; Xu, Xin; Zheng, Bixia; Wang, Chunli; Zhou, Wei; Tang, Jian; Zhao, Xiaoke (Frontiers in Pediatrics, 2023)
Biallelic TENM3 variants were recently reported to cause nonsyndromic microphthalmia with coloboma-9 (MCOPCB9) and microphthalmia and/or coloboma with developmental delay (MCOPS15). To date, only 8 syndromic and nonsyndromic microphthalmia cases with recessive TENM3 variants have been described. Herein, we report two unrelated new cases with biallelic variants in TENM3, widening the molecular and clinical spectrum. In patient 1, WES revealed compound heterozygous variants in the TENM3 gene: c.3847_3855del; p.Leu1283_Ser1285del and c.3698_3699insA; p.Thr1233Thrfs*20 in the index patient presenting with bilateral microphthalmia, congenital cataract, microcephaly and global developmental delay. In patient 2, compound missense heterozygous variants in the TENM3 gene were identified: c.941C>T; p.Ala314Val and c.6464T>C; p.Leu2155Pro in a 3 years old boy who presented with congenital esotropia, speech delay and motor developmental delay. The clinical features of these two cases revealed high concordance with the previously reported cases, including microphthalmia, developmental delay. The presence of microcephaly in our patient potentially expands the neurologic phenotype associated with loss of function variants in TENM3, as microcephaly have not previously been described. Furthermore, we showed evidence that missense variants in TENM3 associated with a similar, but milder, ocular features.